2015
DOI: 10.1111/jns.12126
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength comparison in immune‐mediated neuropathies: Vigorimeter vs. Jamar

Abstract: The Jamar dynamometer and Vigorimeter have been used to assess grip strength in immune-mediated neuropathies, but have never been compared to each other. Therefore, we performed a comparison study between these two devices in patients with immune-mediated neuropathies. Grip strength data were collected in 102 cross-sectional stable and 163 longitudinal (new diagnoses or changing condition) patients with Guillain-Barré syndrome (GBS), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), gammopathy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
(45 reference statements)
3
24
1
2
Order By: Relevance
“…Of these 38 articles, 27 were judged to be inappropriate following review of their titles and abstracts. Of the 11 remaining articles, 4 provided acceptable information relevant to the MCID of grip strength9,10,11,12 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Of these 38 articles, 27 were judged to be inappropriate following review of their titles and abstracts. Of the 11 remaining articles, 4 provided acceptable information relevant to the MCID of grip strength9,10,11,12 ) .…”
Section: Resultsmentioning
confidence: 99%
“…IVIg-response is primarily defined in our clinical practice, by a ≥ 1-point improvement of the Overall Neuropathy Limitation Scale (ONLS) [ 7 ], excluding a grade 1 to grade 0 amelioration of the upper limb component, as not functionally meaningful. In those not meeting this requirement, patients are considered as responders if they demonstrate an improvement of ≥ 4 raw points (out of 48) of the inflammatory Rasch-built Overall Disability Scale (I-RODS) [ 8 ], and/or a ≥ 5 kg improvement of Jamar grip strength of the dominant or clinically more affected hand [ 9 , 10 ]. Additionally, we also consider improvements of lesser amplitudes of the I-RODS and Jamar grip as consistent with an IVIg-response, if both are concurrently present, with, in addition, an accompanying Medical Research Council (MRC) Sum Score (MRCSS) improvement by ≥ 2 points.…”
Section: Methodsmentioning
confidence: 99%
“…A study comparing the vigorimeter versus Jamar dynamometer in immune-mediated neuropathies, including CIDP, revealed that significantly more patients preferred the vigorimeter, largely based on hand comfort during testing. 33 Validity, reliability, and responsiveness were similar between the two tools.…”
Section: Grip Strengthmentioning
confidence: 90%